2020
DOI: 10.1111/crj.13176
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the serum albumin level for long‐term prognosis in patients with acute pulmonary embolism

Abstract: Introduction and objectives The aim of this study was to investigate the association of serum albumin (SA) level with long‐term prognosis in patients with acute pulmonary embolism (PE). Materials and methods We retrospectively enrolled 269 patients with acute PE. The SA level was obtained within 12‐24 hours following admission. The primary endpoints were the incidence of short‐ and long‐term mortality in acute PE patients. The mean duration of the study follow‐up was 21 ± 19 months. Results During the follow‐u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…2 Until now, several studies have documented the prognostic value of SA in patients with stable coronary artery disease (CAD), ST elevation myocardial infarction, and pulmonary embolism. 3,4 In this research, 1 the authors also concluded that admission SA level was a strong and independent predictor of all-cause long-term mortality in patients with ACS. Although the research 1 was interesting and well-conducted, we have some comments.…”
mentioning
confidence: 62%
“…2 Until now, several studies have documented the prognostic value of SA in patients with stable coronary artery disease (CAD), ST elevation myocardial infarction, and pulmonary embolism. 3,4 In this research, 1 the authors also concluded that admission SA level was a strong and independent predictor of all-cause long-term mortality in patients with ACS. Although the research 1 was interesting and well-conducted, we have some comments.…”
mentioning
confidence: 62%
“…Albumin, which is the most abundant circulating protein in the body and occupies about 50% of the whole protein content in plasma, plays a critical role in the physiological stage of the body, including osmotic effect, anti-inflammatory activity, anti-thrombus formation, antioxidation and carriers of endogenous and exogenous substances (Caraceni et al, 2013;Arroyo et al, 2014;Hoskin et al, 2020). The first study to find that hypoproteinemia is an independent predictor of longterm mortality from acute pulmonary embolism was conducted in 2018 (Tanik et al, 2020). In addition, this also applies to patients with postoperative acute pulmonary embolism (Pan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…31 In a recent study, the importance of serum albumin level for short-term mortality was identified in a retrospective study of 269 patients. 32 The authors proposed possible explanations that low level of serum albumin may result in deficiency of anti-oxidant function in acute PE patients. 32 The imaging modalities echocardiography and CT can provide information regarding right ventricular dysfunction but other reliable prognostic factors are still lacking.…”
Section: Discussionmentioning
confidence: 99%